PERFORMANSI VIDEO STREAMING PADA JARINGAN LTE (LONG TERM EVOLUTION) MENGGUNAKAN MODE DUPLEX TDD (TIME DIVISION DUPLEX - Wulandari, Asri; Purnomowati, endah Budi; Alfanadiyah, Rizki (Techno Jurnal Ilmu Teknik, 2011)
Video streaming is a technology play video files directly without having to download it. LTE (Long Term Evolution) is a mobile telecommunications technology as the evolution of HSDPA technology. LTE has the ability to transmit data at high speed. LTE network technology used in duplex mode FDD (Frequency Division Duplex) and TDD (Time Division Duplex). This study aims to determine the performance of video streaming on LTE network by using a TDD. The performance is analyzed include delay, packet loss, and throughput. The simulation results prove that the distance between UE and eNodeB with utilization factors influence the end-to-end delay, packet loss, and throughput in streaming video transmission. On the same data packet length, the greater the distance between the eNodeB with the EU, the greater the value of end-to-end delay. While the throughput of the smallest is 352 200 kbps which occurs when the distance between the eNodeB and UE is 10000 m with a utilization factor of 0.9.Â Â Key-word : Video Streaming, LTE, TDD, jarak eNodeB ke UE, faktor utilisasi, delay end to end, packet loss, throughput